Bearing witness to structural violence against migrants and envisioning transnational solidarity. Issue 3 (8th March 2022) - Saleem, Rakhshanda; Li, Peiwei
Abstract: Guided by a critical and transnational framework, this qualitative study centers on the perspectives and analyses of activists and organizers working with migrants to the United States who face devastating conditions due to historical and ongoing exploitation of geopolitical powers and structures of violence. Through thematic and reconstructive analyses, we focus on how 18 participants navigate the intersections of legal, political, economic, and cultural implications, as well as complex ethical and moral dilemmas, tensions, and contradictions that emerged in their work. Grounded in their eyewitness narratives, we attempt to learn about the lived experiences of migrants and engage in critical analysis of structural violence (i.e., violence embedded in the social structures and institutions) and oppressive conditions. We examine the notion of "solidarity" and what it means to engage in anti‐oppressive transnational solidarity with differentials in positionalities and against the backdrop of professional and institutional reproduction of colonial, imperial, racist, and neoliberal forms of structural violence, including within the academy itself. Juxtaposing empirical and structural analyses, we hope to further contribute to a more nuanced understanding of intersectional social struggles and the potential for organizing towards liberatory solidarity. Highlights: Devastating structural violence on migrants resulting from historical and ongoing geopolitics. Consciousness regarding histories of colonialism for transnational solidarity with migrant justice. Critical consciousness of an intersectional anti‐oppression understanding for liberatory organizing.